Analysis on the evolution of precipitation and Runoff characteristics in the east Pi River Basin, China - Nie, Hanjiang; Shen, Zhenqian; Qin, Tianling; Gong, Xinfeng; Huang, Yinghou (Tecnología y ciencias del agua, 2023)
The natural hydrologic cycle is greatly influenced by climate change. In particular, substantial spatiotemporal variations in precipitation can occur in some mountainous areas, and thus it is very important to identify hydrological processes in watershed with high resolution. To analyze the problem above, the Mann-Kendall test, the moving T-test, Sen’s slope estimator and Spearman rank correlation test combined with the spatial interpolation function of ArcGIS, are used to analyze and discuss the evolution of the spatiotemporal distribution characteristics of precipitation and Runoff in a typical small watershed of mountainous areas. The result is precipitation showed a downward trend from south to north and from high-altitude to low-altitude regions. And the difference mainly occurred in the western part of the basin. And the conclusions show the following: 1) An abrupt change in both precipitation and Runoff sequences occurred in 1991; 2) the extreme value of the precipitation trend shifted from the central region to the western region; 3) for the ratio of Runoff in the flood season to annual Runoff, the sequence showed a significant upward trend (95 % confidence level), indicating that the uneven distribution of Runoff has significantly increased since the 1960s.